2016
DOI: 10.1038/ncomms13268
|View full text |Cite
|
Sign up to set email alerts
|

Coupling optogenetic stimulation with NanoLuc-based luminescence (BRET) Ca++ sensing

Abstract: Optogenetic techniques allow intracellular manipulation of Ca++ by illumination of light-absorbing probe molecules such as channelrhodopsins and melanopsins. The consequences of optogenetic stimulation would optimally be recorded by non-invasive optical methods. However, most current optical methods for monitoring Ca++ levels are based on fluorescence excitation that can cause unwanted stimulation of the optogenetic probe and other undesirable effects such as tissue autofluorescence. Luminescence is an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 38 publications
(91 reference statements)
0
115
0
Order By: Relevance
“…Receptors were reconstituted into HEK293T/17 cells together with firefly luciferase-based GloSensor-22F cAMP sensor (Binkowski et al, 2011) or CalfluxVTN Ca 2+ sensor (Yang et al, 2016) that report real time fluctuations in second messenger levels by changes in luminescence and BRET signal, respectively. Consistent with previous reports (Sugamori et al, 1995; Han et al, 1996), we observed that application of DA to cells expressing either dDA1 or Damb stimulated cAMP production (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Receptors were reconstituted into HEK293T/17 cells together with firefly luciferase-based GloSensor-22F cAMP sensor (Binkowski et al, 2011) or CalfluxVTN Ca 2+ sensor (Yang et al, 2016) that report real time fluctuations in second messenger levels by changes in luminescence and BRET signal, respectively. Consistent with previous reports (Sugamori et al, 1995; Han et al, 1996), we observed that application of DA to cells expressing either dDA1 or Damb stimulated cAMP production (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Ligand bindinginduced structural changes in both the GAFa and the catalytic domains in the full-length PDE5 have been extensively explored by developing a Bioluminescence Resonance Energy Transfer (BRET)-based intramolecular conformational sensor [12]. BRET is being increasingly utilized for monitoring activation of proteins and signaling pathways in live cells [13] [14] [15]. The underlying mechanism behind BRET is the non-radiative transfer of energy from a bioluminescent donor such as Renilla luciferase (Rluc) to a fluorescent acceptor such as GFP 2 (a variant of GFP optimized for excitation by Rluc emission) [16].…”
Section: Introductionmentioning
confidence: 99%
“…CalfluxVTN enabled sensitive imaging of calcium flux in response to stimulation of a rhodopsin photoreceptor. [48] Such measurements were refractory to FRET, as external light interfered with receptor activation. Johnsson and coworkers further developed a universal BRET sensor platform for analyte detection.…”
Section: Monitoring New Facets Of Biologymentioning
confidence: 99%
“…Cellular images were reproduced with permission from ref. 48. (B) Caged luciferins and dioxetanes can report on cellular activities.…”
Section: Figurementioning
confidence: 99%